The Role of Capital and Liquidity in Bank Lending: Are Banks Safer?. (22nd January 2020) - Polizzi, Salvatore; Scannella, Enzo; Suárez, Nuria
Abstract: The aim of this paper is to examine whether and to what extent bank capital requirements and liquidity standards influence the level of bank stability. Our approach is that both capital and liquidity affect lending growth, which in turn affects bank stability. We construct a panel dataset on a sample of 2, 054 commercial banks from 117 developed and developing countries during the 2000–16 period. By applying a two‐stage least squares (2SLS) empirical methodology, our findings show that capital and liquidity have a negative direct impact on the level of bank stability. However, this influence is counteracted by an indirect positive effect through the increased level of credit. Our results are not homogeneous across legal and institutional environments. In particular, we provide evidence on more relevant relationships in countries with higher level of protection of creditor rights and lower restrictions on non‐traditional banking activities. Our empirical findings are robust to different specifications of the empirical model and to potential endogeneity problems. Abstract : It is important to remark that when it comes to the introduction of new regulatory requirements, policymakers should deal not only with the direct effects of their decisions, but also to any indirect transmission mechanism that could completely revert the overall effects of their corrective actions.